Reasons for the Fall of the Liber International Order from the Perspective of World Politics (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
In recent years, the gradual fall of the liberal international order, once heralded as the “end of history”, has become an indisputable fact. The world politics aims to explain changes in the nature and foundational systems of international relations, as well as global and domestic politics. Examining the decline of the liberal international order through the paradigm of world politics can comprehensively elucidate the factors affecting the development of both international relations and domestic politics simultaneously, thereby theoretically unifying the two fields. This paper examines the decline of the liberal international order from the perspective of world politics and posits that its decline is attributable to both internal and external reasons: Internally, the economic foundations, rule enforcement, and value propositions of the liberal international order harbor “the seeds of its own destruction”; externally, the influence of developing countries on the traditional value chain, the revisionist foreign policy of major powers, and the politics of striving for recognition have accelerated the decline of the liberal international order. Ultimately, this paper concludes that the decline of the liberal international order is inevitable and, with the waning of the unipolar pattern, the world order is destined to evolve towards a more equitable and fair direction.Key words: liberal international order, world politics, value chain, internal causes, external causes, equality.